EVALUASI KINERJA GEDUNG TERHADAP SIMPANGAN ANTAR LANTAI AKIBAT BEBAN GEMPA (Studi kasus : Gedung 6 lantai RS Bhayangkara Kab Nganjuk)) - Feisal Feisal Fawwaz Irsyada (Jurnal Vokasi Teknik Sipil, 2025)
RS Bhayangkara Kabupaten Nganjuk, one of the hospitals in Nganjuk, is located in an area with potential earthquake risks. Therefore, its structure must be designed to withstand seismic forces during an earthquake. The studied building has six floors, reaching a height of 28 meters, with most of its space functioning as inpatient rooms. This study aims to evaluate the structural performance of the hospital building against earthquake loads using ETABS V18 software, referring to the seismic-resistant building requirements outlined in SNI 1727:2019. The research results show that the inter-story drift (Inelastic Drift) from the 2nd floor to the roof in both the X and Y directions is below the Drift Limit. The largest drift occurs on the 4th floor in the Y direction, with a displacement of 23.918 mm, which is equal to the Drift Limit of 23.918 mm. Therefore, the Inelastic Drift from the 2nd floor to the roof in both the X and Y directions does not exceed the Drift Limit, ensuring that the structure is safe.